2004
DOI: 10.1364/ao.43.001216
|View full text |Cite
|
Sign up to set email alerts
|

Optical-fiber surface-plasmon resonance sensor with multiple resonance peaks

Abstract: We report on an optical fiber surface plasmon resonance sensor that exhibits multiple resonance peaks. The sensor is based on a uniform-waist single-mode tapered fiber coated on one side with a thin metal layer. Owing to the asymmetry of the sensor structure, the different hybrid surface plasmon modes supported by the semicircular layer can be excited by the fundamental fiber mode. As a result, the sensor transmission spectrum exhibits several dips that depend on the taper waist diameter. The advantages of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 15 publications
2
56
0
Order By: Relevance
“…2,3,16,17 Compared to a single FBG, the FFPI sensors possess narrower resonance peaks and are more desirable for high accuracy wavelength measurement. 2,3,9,18 To that end we propose and demonstrate an etch-eroded FFPI sensor formed by two FBGs. The FFPI sensor is used to measure the refractive index of isopropyl alcohol ͑IPA͒ solutions of different concentrations, exhibiting the capability of detecting very small index variations of the ambient medium.…”
mentioning
confidence: 99%
“…2,3,16,17 Compared to a single FBG, the FFPI sensors possess narrower resonance peaks and are more desirable for high accuracy wavelength measurement. 2,3,9,18 To that end we propose and demonstrate an etch-eroded FFPI sensor formed by two FBGs. The FFPI sensor is used to measure the refractive index of isopropyl alcohol ͑IPA͒ solutions of different concentrations, exhibiting the capability of detecting very small index variations of the ambient medium.…”
mentioning
confidence: 99%
“…Many developments on hybrid fiber SPR sensors can also be found in recent literatures [9][10][11][12]. Here we provide an integrated outlook of fiber-optic sensors advanced by micro-or nano-structure optical fibers with regard to physical characteristics, fabrication methodologies and sensing performance.…”
Section: Introductionmentioning
confidence: 92%
“…This scheme is illustrated in Figure 3. In [16]; a fiber sensor with an asymmetric metal coating on a uniform waist of a single-mode tapered fiber was suggested (a detail is shown in Figure 4). In all these fiber sensors the transmitted guided mode is used in the interrogation process, and a recent review of these fiber sensors can be found in [17].…”
Section: Guided Wave Surface Plasmon Sensorsmentioning
confidence: 99%